Optimasi Segmentasi Citra Daun Kelor dengan Metode Thresholding dalam Identifikasi Penyakit - Yuhana Rambu Dima Mandar; Yustina Rada; Reynaldy Thimotius Abineno (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Diseases in moringa leaves pose a serious threat to PT. Marada Kelor Sumba, a moringa processing company located in Kelurahan Temu, Kanatang District, East Sumba Regency. The main products from moringa processing are moringa powder and moringa tea bags, which are highly beneficial as supplementary food for infants and pregnant women. The company collaborates with the East Sumba Government for the prevention and handling of stunting. The primary objective of this study is to optimize image segmentation methods to identify diseases in moringa leaves with significant implications using MATLAB software. The image segmentation method using Thresholding is applied to separate diseased moringa leaves from healthy ones. Additionally, filters are applied to enhance disease image segmentation capabilities and manipulate images. This research focuses on the image segmentation stage using MATLAB. The benefits of this research are crucial in agriculture and technology development, including early segmentation of diseases in moringa leaves, improvement of disease image segmentation process efficiency, contribution to image-based agricultural technology, and enrichment of scientific knowledge and understanding of disease image segmentation in moringa plants. The segmentation accuracy obtained from testing all samples is 66,67%.